The mechanism of grain growth at general grain boundaries in SrTiO3. (November 2020) - Sternlicht, Hadas; Rheinheimer, Wolfgang; Mehlmann, Alexander; Rothschild, Avner; Hoffmann, Michael J.; Kaplan, Wayne D.
Abstract: In this work anisotropic motion of disconnections at general grain boundaries in SrTiO3 was detected in-situ at 1030 °C, 1040 °C and 1050 °C using transmission electron microscopy. The same anisotropic motion of ledges and terraces at the surfaces of SrTiO3 was detected in-situ. These results corroborate previous ex-situ studies on disconnection motion in SrTiO3, and experimentally confirm that anisotropic disconnection motion is the mechanism of grain growth. Graphical abstract: Image, graphical abstract